At Westonci.ca, we provide clear, reliable answers to all your questions. Join our vibrant community and get the solutions you need. Ask your questions and receive detailed answers from professionals with extensive experience in various fields. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.

What is the solution of x3 – x2 > 9(x – 1)

Sagot :

Consider the cubic equation,

x³ - x² = 9 (x - 1)

We can solve this by factoring:

x³ - x² - 9x + 9 = 0

x² (x - 1) - 9 (x - 1) = 0

(x² - 9) (x - 1) = 0

(x - 3) (x + 3) (x - 1) = 0

So the cubic has roots at x = 3, x = -3, and x = 1. Split the real line into the open intervals (-∞, -3), (-3, 1), (1, 3), and (3, ∞). Check if the inequality holds for some test point taken from each interval:

• in (-∞, -3), take x = -4. Then

(-4)³ - (-4)² = -80

9 (-4 - 1) = -45

but -80 > -45 is not true. So this interval is not in the solution set.

• in (-3, -1), take x = -2. Then

(-2)³ - (-2)² = -12

9 (-2 - 1) = -27

and -12 > -27 is true. So x in (-3, -1) satisfies the inequality.

• in (1, 3), take x = 2. Then

2³ - 2² = 4

9 (2 - 1) = 9

but 4 > 9 is not true.

• in (3, ∞), take x = 4. Then

4³ - 4² = 48

9 (4 - 1) = 27

and 48 > 27 is true.

So, the complete solution set is

(-3, -1) U (3, ∞)

(where U denotes union)